THE MORPHOLOGY AND ONTOGENETIC OF TAREBIA GRANIFERA (LAMARCK, 1822) FROM INDONESIA (GASTROPODA: CERITHIOIDEA: THIARIDAE) - Nur Rohmatin Isnaningsih; Adi Basukriadi; Ristiyanti Marsetiyowati Marwoto (Treubia, 2017)
The freshwater gastropod Tarebia H. Adams & A. Adams, 1854, are found in rivers, lakes, and other limnetic habitats. In Indonesia, Tarebia granifera (Lamarck, 1822) is the only species within the genus that has a wide distribution. The systematics and identity of this species are still doubtful due to high variation in shell morphology, especially shell height and ornamentation or sculpture of shell. To determine the identity of T. granifera from Lombok, Banten, and Maros, ontogenetic studies have been conducted. The results showed that T. granifera from Lombok produce the highest number of embryonic shells. The number of progeny in the brood pouch from a single individual of T. granifera can vary between 9 to 203 embryonic shells which are found in various stages of 0.22 mm to about 5 mm in size inside the brood pouch.